2022
DOI: 10.3389/fnsyn.2022.857608
|View full text |Cite
|
Sign up to set email alerts
|

Resilient Hippocampal Gamma Rhythmogenesis and Parvalbumin-Expressing Interneuron Function Before and After Plaque Burden in 5xFAD Alzheimer’s Disease Model

Abstract: Recent studies have implicated impaired Parvalbumin Fast-Spiking Interneuron (PVIN) function as a precipitating factor underlying abnormalities in network synchrony, oscillatory rhythms, and cognition associated with Alzheimer’s disease (AD). However, a complete developmental investigation of potential gamma deficits, induced by commonly used carbachol or kainate in ex vivo slice preparations, within AD model mice is lacking. We examined gamma oscillations using field recordings in acute hippocampal slices fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 113 publications
(176 reference statements)
1
2
0
Order By: Relevance
“…Interestingly, no changes were observed in either the amplitude or frequency of excitatory and inhibitory spontaneous synaptic events (Fig. 6 H, I ) echoing recent work from 3-month-old 5xFAD mice in hippocampal slices, where local circuit behavior and oscillations were also largely resilient to change 95 . This may be due to several factors, including the relatively low AP frequency of evoked PV firing in the slice.…”
Section: Resultssupporting
confidence: 82%
“…Interestingly, no changes were observed in either the amplitude or frequency of excitatory and inhibitory spontaneous synaptic events (Fig. 6 H, I ) echoing recent work from 3-month-old 5xFAD mice in hippocampal slices, where local circuit behavior and oscillations were also largely resilient to change 95 . This may be due to several factors, including the relatively low AP frequency of evoked PV firing in the slice.…”
Section: Resultssupporting
confidence: 82%
“…The shift in the limits for the bandwidth power calculations to 20-80 Hz compared with in vivo (commonly ⁓30-80 Hz) is due to the linear relationship between recording temperature and oscillation frequency [58,59]. In our experimental set-up, the optimal recording temperature was ⁓6 °C lower than the body temperature, and the bandwidth used for gamma power calculation is a routinely used frequency band in ex vivo recordings of gamma rhythms [52,55,[59][60][61][62][63]. Thus, in control conditions all the slices included in the study showed a peak frequency between 20 and 80 Hz.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, in APP/PS1 mice (AD model with human amyloid-beta precursor protein and presenilin-1 mutations), PV INs show close interactions with microglia (Gervais et al, 2022). However, another study has called in to question the relationship between PV INs and AD pathogenesis (Mackenzie-Gray Scott et al, 2022). Of note, PV INs also express amyloid-degrading enzymes which would indeed be counterintuitive (Pacheco-Quinto et al, 2016).…”
Section: Pv Insmentioning
confidence: 99%